Four years of immunization with OM-85 BV to prevent respiratory infections in HIV+ patients - Capetti, Amedeo (Landes Bioscience, 2013)
We report an interventional, non-randomized experience of OM-85 BV immunization in a group of 104 HIV-infected subjects presenting recurrent seasonal respiratory bacterial infections. We compared the number of respiratory events, the use of antibiotics and the cost related to antibiotics before (2005–2006) and after (2008–2011) the introduction of such intervention. The year 2007 was excluded from the analysis since half of the patients were immunized in that year in an exploratory approach. Respiratory infections dropped in all groups but in subjects with recurrent otitis, leading to a reduction in the use of antibiotics. This is the first report of the effect of OM-85 BV in vivo in HIV-infected subjects.